Place references in Chinese music titles since 1912: changing patterns across regions and time - Xueting Hong (Springer Nature, 2021)
Abstract There are strong links between music and ‘sense of place’. This study investigates the connotations and features of the sense of place in songs against the background of social change between 1912 and 2019 in China. From 1912 through 1949, the sense of place was chiefly patriotic. From 1950 to 1979, the influence of socialism resulted in songs that concentrated on historical sites to form place identity. After 1980, the music market influenced the writing of songs about ‘place’. Since 2010, the sense of place has involved the activities of individuals and events within an area that shape the feel and impression of the place, and it is complex and plentiful. The results indicate that the relationships between people and the places they sing about become more abundant and detailed over time, along with a change from each place having a dominant style to a more diverse scenario. Before the opening-up and reform of China in 1979, the sense of place was often a shared collective memory, whereas today, the trend is towards personal songs. Additionally, sense of place is studied in regard to social processes as well as individual music pieces, and the driving force of each period is the response to basic social contradictions.